2011
DOI: 10.1002/hon.988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of second‐generation tyrosine kinase inhibitors towards osteogenic differentiation of human mesenchymal cells of healthy donors

Abstract: The BCR-ABL inhibitor imatinib is a standard first-line therapy for patients with chronic myeloid leukemia. However, it has been demonstrated that this long-term treatment is associated with altered bone metabolism. The mechanisms of this effect are not fully understood, but an inhibition of the platelet-derived growth factor receptor (PDGF-R) β axis has been suspected on the basis of some in vitro findings. We evaluated the osteoblastic differentiation of mesenchymal stem cells derived from bone marrow (hBM-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…In this perspective, we [21] and others [22-25] have demonstrated that in CML patients treated with IM there is a transient increase in bone-formation markers that could be linked to inhibition of PDGFR signaling. We have also demonstrated that also NI induced osteoblastogenesis in vitro, probably triggering the same IM targets [26]. Therefore the increase of SPARC induced by TKIs could be related to the well documented modification of the bone metabolism observed in IM treated patients.…”
Section: Discussionmentioning
confidence: 87%
“…In this perspective, we [21] and others [22-25] have demonstrated that in CML patients treated with IM there is a transient increase in bone-formation markers that could be linked to inhibition of PDGFR signaling. We have also demonstrated that also NI induced osteoblastogenesis in vitro, probably triggering the same IM targets [26]. Therefore the increase of SPARC induced by TKIs could be related to the well documented modification of the bone metabolism observed in IM treated patients.…”
Section: Discussionmentioning
confidence: 87%
“…However, the reported findings significantly disagreed [56][58]. Jonsson and colleagues showed that dasatinib inhibits the proliferation of MSC and their bone morphogenetic protein-dependent osteoblastic differentiation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, these findings could be also documented during treatment with other TKIs such as nilotinib and dasatinib [47,48]. Some reports also described cases of worsening of hypothyroidism or thyroid abnormalities during Imatinib and 2 nd generation TKIs, which needed increased dosages of hormone supplementation [49].…”
Section: Th Anniversary Issuementioning
confidence: 69%